ANALISIS KEEKONOMIAN PEMBORAN SUMUR MULTILATERAL PADA RESERVOIR HETEROGEN BERTENAGA DORONG AIR DENGAN ANALISIS MULTIVARIAT - Kunto Bisono, Sidik
Advance in science and technology that applied in drilling and production technology have resulted well with modern design. Multilateral drilling has been a new innovation in oil industry. Multilateral drilling is new technology to create a well with mutiple branches in order to enhance well productivity. Although multilateral wells result in higher well productivity, they are costly and risky. Multilateral drilling design is related with number of branch and its length. Increasing number of branch and its length will enhance productivity index which affects recovery factor and economical aspect. Differences in rock properties penetrated by well and well completion will also give various results. Therefore, optimization of drilling design is required in order to obtain optimum results in economical aspect. This paper presents about the influence of these variables to economical aspect of multilateral drilling project in heterogeneous and water drive reservoir. By knowing the influence of each variable above, it can be obtained a consideration in multilateral drilling design. To achieve this, the influence of these variables has been studied with statistical software using SPSS. The results of this analysis indicate that number of branch and its length further affect the economic value than other variables.